(untitled) (Plant Tissue Culture and Biotechnology, 2008)
Healthy multiple shoot regeneration was observed from petiole-attached cotyledon (PC) explants of CVL-1 on MS containing 0.2 mg/l BAP and 1.0 mg/l IAA. On the other hand, the best response for multiple shoot regeneration in CVE-3 was obtained when the same explants were cultured on MS with 2.5 mg/l BAP and 0.5 mg/l NAA. However, the same explant of D-154 was found to show less responsive compared to other two varieties to produce multiple shoots. Cotyledonary nodal explants of all the three varieties were found to produce maximum number of multiple shoots on MS supplemented with 0.2 mg/l BAP and 1.0 mg/l IAA. Best root induction was observed at the base of the in vitro regenerated shoots on half the strength of MS supplemented with 0.3 mg/l IBA. The in vitro grown plantlets were successfully transplanted into soil. They grew up to maturity, flowered and fruited like the control plants. Key words: Regeneration, White jute, Corchorus capsularis DOI = 10.3329/ptcb.v17i1.1116 Plant Tissue Cult. & Biotech. 17(1): 11-18, 2007 (June)